Analisis Perbandingan Arus Kas Sebelum Dan Selama Pandemi Covid-19 Pada Perusahaan Makanan Dan Minuman Terdaftar Di Bursa Efek Indonesia - Irmawati, Irmawati (Fakultas Ekonomi Universitas Gresik, 2021)
This study aims to find out whether there are significant differences between the cash flow statements before and during the Covid-19 pandemic for food and beverage companies listed on the Indonesia Stock Exchange. The analytical method used is descriptive analysis, which is an analysis that provides an overview of the data obtained from the research results. Normality test using the KolmogorovSmirnov one sample test, and hypothesis testing using the Wilcoxon signed rank test. The results of this study indicate that there is no significant difference between the cash flow statements before and during the Covid-19 pandemic for food and beverage companies listed on the Indonesia Stock Exchange.